미지정수 수준 조정을 고려한 다중클러스터 시스템 효율화 방안 - 유선경; Sunkyoung Yu; 송준솔; Junesol Song; 기창돈; Changdon Kee (한국항행학회논문지, 2017)
최근 동적 사용자의 정밀위치 요구가 높아지면서, Network RTK(real time Kinematics)를 동적사용자에게 적용하는 방안 연구가 활발히 진행되고 있다. Network RTK는 다수의 기준국 반송파 측정치를 활용해 약 50-70km 영역에 정밀위치를 제공하는 시스템이다. 이러한 Network RTK 보정정보를 제공하는 다수의 클러스터를 하나의 시스템으로 구성하면, 보다 넓은 영역의 동적 사용자에게 정밀위치를 제공할 수 있다. 본 논문은 다중 클러스터를 전국으로 확장하는 경우 효율적으로 운용하는 방안에 대해 연구했다. 다중 클러스터 시스템의 구성에 따른 계산량을 분석하고, 효율적인 운용을 위해 주 수신국 운용 방안 및 시스템 인프라 구성 방안을 제안했다. 또한 각 제안한 방안에 따른 효과를 분석하고자, 국토지리정보원의 기준국을 활용해 71개의 클러스터를 구성하여, 시뮬레이션을 수행했다. 시뮬레이션 결과 주 수신국 운용 방안에 따라 시스템 계산량은 66 % 감소하고, 시스템 구성에 따라 시스템 구성비용을 90 % 절감할 수 있었다. As the demand of high accuracy positioning for dynamic users increases, Network RTK is actively researched for dynamic users. Network RTK is a system which provides precise positioning in the range of about 50 to 70km radius using carrier phase measurements from several reference stations. By configuring multiple clusters, which provide Network RTK corrections independently, as a single system, it could provide precise positioning for a wider area. In this paper, we have studied how to efficiently operate multiple clusters in the Korean Peninsula. We analyzed the computational load according to the configuration of a multi-cluster system and proposed a method of selecting the main reference station and system infrastructure configuration for efficient operation. In order to analyze the effects of each proposed method, 71 clusters were constructed using the reference stations of the National Geographic Information Institute and simulations were conducted. As a result of the simulation, system computation amount was reduced by 66 % and system configuration cost was reduced by 90 %.